The anti-PD-L1/CTLA-4 bispecific antibody KN046 plus lenvatinib in advanced unresectable or metastatic hepatocellular carcinoma: a phase II trial - Da Xu; Hongwei Wang; Quan Bao; Kemin Jin; Ming Liu; Wei Liu; Xiaoluan Yan; Lijun Wang; Yanqiao Zhang; Guangyu Wang; Yue Ma; Zhigang Ma; et al. (Nature Communications)
Abstract This open-label phase II trial (NCT04542837) aimed to evaluate the efficacy and safety of KN046 combined with lenvatinib in patients with advanced hepatocellular carcinoma (HCC), and explore the potential response biomarkers. Participants received KN046 5 mg/kg every 3 weeks and lenvatinib 12 or 8 mg once daily. The primary endpoints were safety, tolerability, dose-limiting toxicity (DLT), and objective response rate (ORR) according to RECIST v1.1. A total of fifty-five participants were enrolled. The results meet the pre-specified primary endpoints. No DLT was observed in the safety run-in period. The incidence of serious adverse events and grade ≥3 treatment-related adverse events (TRAEs) was 30.9% and 47.3%, respectively. Grade ≥3 immunotherapy-related adverse events occurred in 3 (5.5%) participants. Five (9.1%) participants discontinued treatment due to TRAEs, all of which were grade 1-2. The ORR was 45.5% (95% CI, 31.97-59.45). The median progression-free survival was 11.0 (95% CI, 8.21-15.24) months. The median overall survival (OS) was 16.4 (95% CI, 11.20-not estimable) months, and 12-month OS rate was 60.0% (95% CI, 45.87-71.55). Circulating tumor DNA status before the third cycle of treatment was associated with prognosis. In conclusion, First-line KN046 plus lenvatinib shows promising efficacy for advanced unresectable or metastatic HCC.